2002
DOI: 10.1074/jbc.m201781200
|View full text |Cite
|
Sign up to set email alerts
|

CD45 Controls Interleukin-4-mediated IgE Class Switch Recombination in Human B Cells through Its Function as a Janus Kinase Phosphatase

Abstract: CD45 plays a critical regulatory role in receptor signaling through its protein tyrosine phosphatase and Janus kinase (JAK) phosphatase activities. To investigate whether CD45 also plays a regulatory role in Ig class switching in human B cells, we examined the effects of CD45 triggering on Ig class switching to IgE and its relationship with CD45 JAK phosphatase activity. Anti-CD45 triggering of CD45 significantly inhibited interleukin-4 ؉ anti-CD40-induced switch recombination in a switch recombination vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
(43 reference statements)
4
30
1
1
Order By: Relevance
“…DC-PCR for Human S-S⑀ Recombination-DC-PCR was performed as described (16) and was used to quantify the levels of S-S⑀ recombination in stimulated primary human B cells. Genomic DNA was digested with BglII followed by ligation under conditions favoring selfligation.…”
Section: Methodsmentioning
confidence: 99%
“…DC-PCR for Human S-S⑀ Recombination-DC-PCR was performed as described (16) and was used to quantify the levels of S-S⑀ recombination in stimulated primary human B cells. Genomic DNA was digested with BglII followed by ligation under conditions favoring selfligation.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that CD45, via its JAK phosphatase activity, is able to negatively regulate IgE CSR in human B cells through inhibition of IL-4 plus anti-CD40-induced Ig ⑀ germline transcription (35). However, whether CD45 plays a role in AID expression is not known.…”
mentioning
confidence: 98%
“…We have previously shown that CD45 functions as a JAK phosphatase to negatively regulate IL-4-dependent IgE CSR via inhibition of Ig ⑀ germline transcription (35). To investigate whether IL-4-dependent AID induction is also regulated by CD45 signaling, we examined the effect of anti-CD45 on IL-4-dependent AID induction, as well as on Ig ⑀ germline transcripts, in BL-2 cells.…”
Section: Il-4-induced Aid Expression Is Negatively Regulated By Cd45 mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Src family kinases were identified as primary molecular targets for CD45, targeted disruption of the CD45 gene leads to enhanced cytokine and IFN receptor-mediated activation of JAKs and STAT proteins. In vitro, CD45 directly dephosphorylates and binds to JAKs and negatively regulates IL-3-mediated cellular proliferation, Epo-dependent hematopoiesis, IFN-mediated antiviral responses (Irie-Sasaki et al, 2001) and IL-4/anti-CD40-induced switch recombination (Yamada et al, 2002).…”
Section: Negative Regulation Of Janus Kinases-signal Transducers and mentioning
confidence: 99%